Detection of Serum IgG Specific for Brachyspira pilosicoli and “Brachyspira canis” in Dogs - Julia Gothe; Matthias Horn; Christoph G. Baums; Romy M. Heilmann; Wieland Schrödl (Veterinary Sciences, 2024)
Brachyspira pilosicoli (B. pilosicoli) is a pathogen in pigs, poultry, and humans causing colitis, diarrhea, and poor growth rates. Its role as a canine pathogen is controversial, and the seroprevalence of specific IgG antibodies against B. pilosicoli in dogs is unknown. A further, not yet officially recognized Brachyspira species in dogs is “Brachyspira canis” (“B. canis“), which is proposed to be apathogenic. This study evaluates enzyme-linked immunosorbent assays (ELISAs) measuring serum IgG antibodies specific for B. pilosicoli or “B. canis” and investigates levels of specific IgG antibodies against B. pilosicoli and “B. canis” in a cohort of clinical patients presented at an animal referral clinic. These ELISAs use detergent-extracted antigens from B. pilosicoli and “B. canis”. To increase analytic specificity, we precipitated the antigens with trichloroacetic acid (TCA) to isolate and concentrate the respective protein fraction. Our results indicate that a large number of serum IgG antibodies bind to shared epitopes of detergent-extracted antigens of the two spirochaetes. Our data also suggest that dogs might not only carry B. pilosicoli but also have “B. canis”-specific serum IgG antibodies.